(untitled) (Indian Journal of Public Health Research & Development, 2020)
Purpose: The purpose of this study was to analyze the effect that self-efficacy and wisdom on job competence in care worker in Korea. Method: The subjects of this study were 123 care workers. The data were analyzed using descriptive statistics, t-test, ANOVA, Pearson’s correlation coefficient and stepwise multiple regression using the SPSS Window 23.0 program. Results: The care workers’ self-efficacy scored 3.80 points out of 5 points, and wisdom scored 3.63 points out of 5 points, and job competence scored 3.66 points out of 5 points. The job competence of care workers was a high positive correlation with self-efficacy (r=.53, p<.001), wisdom (r=.72, p<.001). The wisdom (?=.715, p<.001) of care workers had a significant influence on job competence, showing a 51.1 percent explanation power. Conclusion: The self-efficacy and wisdom of care workers showed a positive correlation with job competence, the higher the degree of self-efficacy and wisdom was found to be, the higher the job competence. Wisdom is the most influential variable on the job competence of care workers. Therefore, in order to improve the health and quality of life of the elderly who living at home by increasing the job competence of the care workers, it is necessary to provide the intervention program so that self-efficacy and wisdom can be developed. Especially, wisdom has the attribute that can be acquired through experience while living, so it is also necessary to train them to make a successful resolution in response to various problems. This study is aimed at the care workers who provide home care, so it is suggested that the study is repeated targeting the care workers who work in the hospital by expanding the institution.